Virginás, Andrea (ed.): Cultural Studies Approaches in the Study of Eastern European Cinema: Spaces, Bodies, Memories. - Pócsik, Andrea (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2018)
Andrea Pócsik’s Review of Andrea Virginás’s edited book Cultural Studies Approaches in the Study of Eastern European Cinema